Addressing the Threat of Emerging Viral Infections - Kawaoka, Yoshihiro (Keio journal of medicine, 2023)
Emerging infections are caused when microorganisms that are maintained in a reservoir where they cause no harm, transmit from the reservoir to a new host. I have been studying the replication, molecular basis for pathogenesis, and host responses to emerging viruses, including influenza virus, Ebola virus, and SARS-CoV-2, and using the knowledge gained from these studies to develop antivirals and vaccines.Influenza viruses cause epidemics every winter, but occasionally new influenza viruses emerge and spread worldwide (pandemic). We established a technique that allows us to make influenza viruses artificially. This technique is now widely used for basic research and for the development of vaccines against highly pathogenic avian influenza virus for pandemic preparedness and live attenuated influenza vaccines. Using this technique, we elucidated the mechanisms of emergence of pandemic viruses, viral replication, and the molecular mechanism of pathogenesis.Ebola virus causes severe disease with a mortality rate of up to 90%. In 2013, a major outbreak of Ebola virus began in West Africa that led to nearly 30,000 people being infected and a death toll of over 10,000 people. During the outbreak, we established a laboratory in Sierra Leone and used samples from Ebola patients to study host responses and identify biomarkers for severe infection. We also established a technology to artificially make Ebola virus and used this technology to make an Ebola virus that grows only in a particular cell line. Using this virus, we produced an inactivated Ebola vaccine, which was shown to be safe and effective in a Phase I clinical trial.Late in 2019, SARS-CoV-2 emerged in Wuhan, China and has since caused unprecedented damage globally. In our laboratory, we established an animal model for this infection and have used it to evaluate pathogenicity, efficacy of therapeutic monoclonal antibodies and antivirals, and to develop vaccines.In my presentation, I will discuss our findings regarding these emerging viral infections.